Death in the Garden City - Dams, Jeanne M (Dams, Jeanne M. Dorothy Martin mysteries, 2019)
"When Dorothy Martin and her ex-policeman husband Alan are asked by some good friends to look into a series of petty crimes that are perplexing the local Mounties in the picturesque Canadian city of Victoria, they immediately jump on a plane to British Columbia and settle themselves into the heart of the local community. Drinking champagne with the local businessman and would-be politician as well as cups of tea with the local recluse, they infiltrate all ranks of Victoria society. But when a young woman goes missing and a body is discovered, it would appear that the petty crimes have turned deadly. With their ability to get to the root of a crime and dig out the culprit, it's not long before Dorothy and Alan realize they have embarked on a trip that will become far more dangerous than they ever envisaged."--Provided by publisher.